Vision as Supervision: The Case of the Pre-Raphaelite Shakespeare - Jukić-Gregurić, Tatjana (Array, 2000)
Painters of the Pre-Raphaelite Brotherhood considered Shakespeare's plays one of the most significant sources of their paintings. Given the fact that Shakespeare's plays were written for the stage - that their performative potential requires vision and visuality - the Pre-Raphaelite revisions of his text involve a highly peculiar anxiety about the authority of Shakespeare's vision, and the impact of too close an encounter of the visual and the scriptural. Taking into consideration New Historicist readings of Shakespeare's theater and its politics, my paper will address the iconicized Shakespeare of the Pre-Raphaelite Brotherhood in terms of the politics of its intermedial practice.